Pengelolaan Limbah Rumah Tangga Berbasis Komunitas untuk Produksi Pupuk Kompos Organik - Alam, Yuniar; Harliana, Harliana; Haryuni, Nining; Oktaviani, Ragil Tri (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Household waste, which is mostly organic waste, such as leftover food, vegetables, fruit peels, and food processing waste, has the potential to pollute the environment if not managed properly. This community service aims to improve the knowledge and skills of the people of Sumberkepuh Village, Wonosari Hamlet, in utilizing household waste into organic compost. This program aims to reduce odor pollution and methane gas emissions and promote environmentally friendly waste management. The partners of this activity are local housewives and farmers. The method used is Participatory Action Research (PAR), which involves delivering materials, interactive discussions, demonstrations of organic waste processing, and question and answer sessions. The results of the activity showed an increase in the community's understanding and skills in processing organic waste into compost. This program received a positive response from participants, who are now more motivated to manage household waste independently and sustainably.